Role of Arbuscular Mycorrhiza in Heavy Metal Tolerance in Plants: Prospects for Phytoremidiation - Panda2, Mrinal Kanti Bhattacharjee1; Sakhi Dutta1, Hrishikesh Upadhyaya1*, Sanjib Kumar (Journal of Phytology, 2010)
Arbuscular Mycorrhiza (AM) is an obligate biotroph, which mainly improves phosphorus nutrition, ability to withstand water stress and offers a natural potential for biological control of root pathogen. They are also reported to be present on the roots of plants growing on metal-contaminated soils and play an important role in metal tolerance and accumulation. Isolation of the heavy metal tolerant AM fungi can be a potential biotechnological tool for inoculation of plants for successful phytoremediation. AM fungi provide an attractive system to advance plant-based environmental clean-up. During symbiotic interaction the hyphal network functionally extends the root system of their hosts. Thus, plants in symbiosis with AM fungi have the potential to take up heavy metal (HM) from an enlarged soil volume. This review throws light on the potential and the prospects of AM fungi in heavy metal tolerance of plant and its utilization for enhancing phytoremediation of heavy metal contaminated soils. Key words: Arbuscular Mycorrhiza (AM), Heavy metal, Phytoremediation <span style="font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Hrishikesh Upadhyaya et al. Role of Arbuscular Mycorrhiza in Heavy Metal Tolerance in Plants: Prospects for Phytoremidiation. J Phytol 2/7 (2010) 16-27.